2021
DOI: 10.3390/agronomy11112330
|View full text |Cite
|
Sign up to set email alerts
|

DArTseq Genotypic and Phenotypic Diversity of Barley Landraces Originating from Different Countries

Abstract: Landraces are considered a key element of agrobiodiversity because of their high variability and adaptation to local environmental conditions, but at the same time, they represent a breeding potential hidden in gene banks that has not yet been fully appreciated and utilized. Here, we present a genome-wide DArTseq analysis of the diversity of 116 spring barley landraces preserved in the collection of the Polish gene bank. Genetic analysis revealed considerable variation in this collection and several distinct g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 88 publications
4
13
0
Order By: Relevance
“…The genetic diversity analysis for the barley landrace collection in this study identified a total of 210,268 SNPs, which would be impossible by previous methods. The SNPs were distributed almost throughout the whole genome despite they were more density toward the telomeric chromosome regions, and this was also found in other reports [7,37]. Therefore, the results based on these SNP markers will be more accurate and useful.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…The genetic diversity analysis for the barley landrace collection in this study identified a total of 210,268 SNPs, which would be impossible by previous methods. The SNPs were distributed almost throughout the whole genome despite they were more density toward the telomeric chromosome regions, and this was also found in other reports [7,37]. Therefore, the results based on these SNP markers will be more accurate and useful.…”
Section: Discussionsupporting
confidence: 72%
“…The two kinds of molecular markers of SSR and SNP are the most commonly used in barley genetic diversity analysis [4][5][6][7][8]15,[26][27][28][29][30][31][32][33][34]. SSR markers were once very popular because of their good stability and easy operation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations